Application of neural network technology to diagnose DC turnouts - Havryliuk, V. I.; Dub, V. Yu.; Malovichko, V. V. (Science and Transport Progress, 2010)
In the paper a procedure of diagnostics and check of failures of switches with DC electric engines on the basis of neural networks is proposed by the authors.